2023
DOI: 10.1002/cnr2.1814
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of monoclonal gammopathy in Morocco – A hospital‐based study

Abstract: Background Monoclonal gammopathies are a group of disorders associated with clonal proliferation of plasma cells that produces a monoclonal protein. Aims The main objective of this study was to describe the epidemiological and immunochemical characteristics of monoclonal gammopathies diagnosed during 19 years in a Moroccan teaching hospital. Materials and Results This retrospective study enrolled 443 Moroccan patients with monoclonal gammopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…A two to three-fold increase in the relative risk for viral and bacterial infections has been documented in patients with MGUS [11]. It is known that both humoral and cellular immunity are affected [11], with impairment of antibody production, function of T-cells, natural killer (NK) cells, and dendritic cells [10,11]. This immune dysregulation likely made our patient susceptible to prolonged skin infection with an uncommon pathogen.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…A two to three-fold increase in the relative risk for viral and bacterial infections has been documented in patients with MGUS [11]. It is known that both humoral and cellular immunity are affected [11], with impairment of antibody production, function of T-cells, natural killer (NK) cells, and dendritic cells [10,11]. This immune dysregulation likely made our patient susceptible to prolonged skin infection with an uncommon pathogen.…”
Section: Discussionmentioning
confidence: 72%
“…Monoclonal Gammopathy of Undetermined Significance is considered an early stage of multiple myeloma (MM), where the production of monoclonal protein is present without systemic effects. It is estimated that 1% of MGUS progress to MM yearly [10]. Patients with MGUS also have a higher rate of renal disease, ischemic heart disease, peripheral neuropathy, and infections compared to those without MGUS [11].…”
Section: Discussionmentioning
confidence: 99%
“…Migkou et al [ 2 ] reported in their work on a total of 852 patients, 100 (12%) cases identified as oligo-secretory/non-secretory of which 20 (2.3%) were true non-secretors. A Moroccan study of 443 MM cases identified five patients with NSMM (2.26%) [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mean age was less than 65 years. Other studies [ 3 , 4 ] also concluded that NSMM patients were younger, with an average age of 57.80 years [ 3 ] and 56 years [ 4 ], respectively. In the present study, the patient was 53 years old, in line with cases reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation